E3 ligase FBXW7 aggravates TMPD-induced systemic lupus erythematosus by promoting cell apoptosis - Chong, Zhenlu; Bao, Chunjing; He, Jia; Chen, Tianxiao; Zhong, Lijia; Li, Gaopeng; Li, Huanle; Fang, Lutong; Song, Yinjing; Fu, Guoxiang; Yang, Xuyan; Lai, Lihua; et al. (Cellular & molecular immunology, 2018)
Systemic lupus erythematosus (SLE) is a systemic autoimmune disease, and the pathogenesis of SLE has not been fully elucidated. The E3 ubiquitin ligase FBXW7 has been well characterized in cancer as a tumor suppressor that can promote the ubiquitination and subsequent degradation of various oncoproteins; however, the potential role of FBXW7 in autoimmune diseases is unclear. In the present study, we identified that FBXW7 is a crucial exacerbating factor for SLE development and progression in a mouse model induced by 2, 6, 10, 14-tetramethylpentadecane (TMPD). Myeloid cell-specific FBXW7 -deficient (Lysm + FBXW7 f/f ) C57BL/6 mice showed decreased immune complex accumulation, glomerulonephritis, glomerular mesangial cell proliferation, and base-membrane thickness in the kidney. Lysm + FBXW7 f/f mice produced fewer anti-Sm/RNP and anti-ANA autoantibodies and showed a decreased MHC II expression in B cells. In Lysm + FBXW7 f/f mice, we observed that cell apoptosis was reduced and that fewer CD11b + Ly6C hi inflammatory monocytes were recruited to the peritoneal cavity. Consistently, diffuse pulmonary hemorrhage (DPH) was also decreased in Lysm + FBXW7 f/f mice. Mechanistically, we clarified that FBXW7 promoted TMPD-induced cell apoptosis by catalyzing MCL1 degradation through K48-linked ubiquitination. Our work revealed that FBXW7 expression in myeloid cells played a crucial role in TMPD-induced SLE progression in mice, which may provide novel ideas and theoretical support for understanding the pathogenesis of SLE.